Análise incremental construtiva de edificações - Kripka, Moacir (1990)
The study of the significance of the consideration of loading and construction sequences in building analysis is the aim of this work. In order to reach this objective a computer program, based on the displacement method, was developed. This program performs the analyses by the conventional procedure and by the incremental constructive procedure. The latter one allows computation of final stresses as well as of the stresses in any construction phase, being possible to model the shoring process, the masonry construction and the research of the maximum and minimum stresses, among other facilities. The presented numerical examples have shown that the conventional procedure does not give good results, being therefore important to use the incremental constructive procedure to obtain a reliable simulation of the real conditions to which structures are submitted.